Desert truffles in the Maamora Forest, Morocco: local nomenclature, harvesting practices, ethnoecology, ethnophenology, and resource availability - Fellaki, Anas; Abourouh, Mohamed; Elyacoubi, Houda; Elyamani, Asmaa; Rochdi, Atmane (Ethnobotany Research and Applications, 2026)
Background: Desert truffles are regarded as noble delicacies with multiple medicinal properties, attracting strong scientific interest worldwide. Maamora Forest, where some of them have been harvested for centuries, provides a privileged setting for studying traditional practices. Thus, this study explores these practices, along with ethnoecological and ethnophenological knowledge they encompass, as well as the threats and behaviors that may compromise sustainability. Methods: This ethnomycological survey, conducted among 149 truffle hunters across the five Maamora Forest cantons, was based on a semi-structured questionnaire complemented by personal field observations. The specimens collected from the pickers were identified using molecular analyses. Collected data were analyzed using descriptive statistics, Pearson’s Chi-square test, Multiple Correspondence Analysis, non-metric Multidimensional Scaling, and Variance Permutational Multivariate Analysis. Results: Results show that desert truffle harvesting is mainly practiced by elderly, unemployed individuals, particularly married women. They are often experienced and regular gatherers. Significant differences were noted across cantons regarding local nomenclature and harvesting practices. Study also highlights a deep empirical understanding of phenology. Main factors threatening sustainability of this resource are overgrazing, urbanization, drought, reforestation with exotic species, and use of pickaxes. Premature harvesting, overexploitation and poor post-harvest practices also contribute to truffle habitats degradation and substantial losses of a large part of the harvest. Conclusions: This work constitutes the first ethnomycological assessment of desert truffles in the Maamora Forest. It enriches local ecological knowledge and supports future research in ecology and biodiversity conservation, while advocating for integrated sustainable management strategies including awareness-raising, cooperative structuring, and domestication trials. Keywords: Ethnomycology, Knowledge transmission, Truffle hunter, Truffle sustainability, Delastria rosea, Tuber oligospermum, Terfezia arenaria.